A quadratic equation has two roots. Let the roots be a and b. The equation can be written as:
(x - a)(x - b) = 0
=> x^2 - ax - bx + ab = 0
=> x^2 - x(a + b) + ab = 0
It is given that the sum of the roots is 125 and the product is 98. Substituting these values gives x^2 - 125x + 98 = 0
The quadratic equation with sum of roots 125 and product of roots 98 is x^2 - 125x + 98 = 0.
Quadratic equations should contain at least two numbers which can de subduded in the equation.
In this case there are 125 and 98
Form a equation in terms of y
Subtitue it in the product equation
The equation is y^2-125y-98=0